Cholesterol-induced LRP3 downregulation promotes cartilage degeneration in osteoarthritis by targeting Syndecan-4 - Chenxi Cao; Yuanyuan Shi; Xin Zhang; Qi Li; Jiahao Zhang; Fengyuan Zhao; Qingyang Meng; Wenli Dai; Zhenlong Liu; Wenqiang Yan; Xiaoning Duan; Jiying Zhang; et al. (Nature Communications, 2022)
This study demonstrates a role of cholesterol metabolism-related gene, Lrp3, in cartilage degeneration and osteoarthritis pathogenesis. LRP3 positively regulates cartilage extracellular matrix metabolism by targeting syndecan-4 via Ras signalling, implicating the cholesterol-LRP3-SDC4 axis in osteoarthritic cartilage degeneration.